Application of jet propellant-8 to premixed charge ignition combustion in a single-cylinder diesel engine. (January 2015) - Park, Youngsoo; Bae, Choongsik; Mounaïm-Rousselle, Christine; Foucher, Fabrice
The aviation fuel, jet propellant-8, was applied to premixed charge ignition combustion as well as conventional combustion in a single-cylinder diesel engine and was compared with diesel fuel. The engine performance and emissions were tested with and without exhaust gas recirculation under two operating conditions. The liquid- and vapor-phase penetration of diesel fuel and jet propellant-8 were also compared by Mie-scattering and Schlieren method under evaporating conditions using a constant-volume chamber. It was observed that jet propellant-8 exhibited slightly longer vapor-phase penetration and evidently shorter liquid-phase penetration compared with diesel fuel due to the lower distillation temperature and density of jet propellant-8. However, despite the faster evaporation rate of jet propellant-8, it was found that the ignition delay with jet propellant-8 was 2–3 crank angle degrees longer than that with diesel fuel due to its lower cetane number. This result was consistent for all operating conditions and combustion regimes. Jet propellant-8 also showed lower nitrogen oxides (NOx ) and smoke emissions for both combustion regimes under the low-load condition because of locally leaner air–fuel mixture caused by longer ignition delay, higher volatility, and lower aromatic contents. As the engine load increased, jet propellant-8 emitted more NOx under conventional combustion regime due to the more vigorous premixed burn phase compared with diesel fuel. With exhaust gas recirculation, jet propellant-8 showed an improved trade-off relationship between NOx and smoke emissions for both combustion regimes due to its better evaporation characteristics and lower aromatic contents. Premixed charge ignition combustion with jet propellant-8 emitted lower smoke than conventional combustion with jet propellant-8 under near-zero NOx level.